Secure Image Role in Online Business Competition - Benny Budiawan Tjandrasa (Integrated Journal of Business and Economics (IJBE), 2019)
Consumer tastes have changed, technology is increasingly sophisticated and communication is no longer constrained by distance and time. Ease and speed of this transaction also support the development of online stores in Indonesia. On the one hand, the presence of online stores has become the main competitor of conventional stores, but on the other hand, the competition between online stores is getting tighter. For this reason, the study discusses several things such as the impact of the development of the industrial revolution on business management from time to time; market potential, benefits and costs of online stores from the perspective of society and government; competition patterns that will be faced between online stores; how do online business site providers survive in the current pattern of competition. This study using exploratory research which aims to photograph developments, market potential, patterns of competition and find ways to survive in online business. Research was conducted by identifying and categorizing previous studies to get various thoughts from previous researchers. Findings of this study showed the potential of the online-store market in Indonesia will grow further along with population growth, but besides the benefits, there are also costs that must be borne by the society and government, for that the government must make strict rules to minimize these losses. Moreover, online-store entrepreneurs must continue to make efficiency while trying to differentiate so that they are not trapped in the pattern of perfect competition market.